Gastroprotective effect test of ekor naga leaves extract (Rhaphidophora pinnata (L.f) Schott) on male white rats - Sani K, Fathnur; Putri, Kresentia; Elisma, Elisma; Lestari, Uce; Maharini, Indri; Yuliawati, Yuliawati (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Rhaphidophora pinnata leaves are one of the herbal plants that have pharmacological effects. Previous research has shown that ekor naga leaves contain secondary metabolites with tonic pharmacological effects, including the ability to heal cut wounds, as well as antihyperglycemic and antidiabetic properties. This research aims to demonstrate the potential of ekor naga leaf extract as a gastroprotective agent. The extract was evaluated using standard methods, including determination of water content, ash content, phytochemical screening, and compound identification by LC-MS. Gastroprotective testing was carried out by dividing the treatment group into six groups, including the Group 1: normal group, Group 2: negative control (Sodium CMC 0.5%),  Group 3: positive control (Sucralfate), Group 4: 125mg/KgBW extract, Group 5: 250 mg/KgBW extract, and Group 6: 500mg/KgBW extract. The results of the observations were in the form of gastric ulcer severity scores and histological images of the gastric organs. Gastroprotective testing revealed significant differences between the treatment groups and the negative control group (p<0.05). The 500 mg/kgBW extract exhibited the most effective gastroprotective effect, with a 42.5% inhibition rate and minimal inflammation observed both macroscopically and microscopically. These results suggest that ethanol extract from ekor naga leaves may serve as an alternative or complementary therapy for gastritis.